El Régimen MYPE Tributario y los beneficios económicos de la formalización en el distrito de Iquitos 2021 - Diaz Silva, Greysi Lucero (2023)
The MYPE tax regime is a regime that currently plays a very important role in the economic development of the country, it could be mentioned that it is the engine of economic movement because it generates a large percentage of the Gross Domestic Product (GDP); in addition, it is the one that provides work to a high percentage of people. MYPES have developed throughout the territory of Peru and in various productive and service sectors, hence the importance for the State to regulate the activities of this tax regime, of course its formalization in accordance with the guidelines established in Law 28015; Thus, it seeks to promote elements that favor its creation, its formalization, its growth and of course its competitiveness in the sector, for that it provides support for new ventures through different means and sectors such as programs, central government, regional governments and local governments; all these activities in the context of a legal framework that is of interest to the private sector, which is the driving force of the country's economic development. This research study entitled "The MYPE Tax Regime and the Economic Benefits of Formalization in the District of Iquitos -2021", established as its general objective to analyze whether the formalization of MYPES in the district of Iquitos period 2021, provided them with economic benefits.